Small airway dysfunction in idiopathic pulmonary fibrosis - Yin, Chengsheng; Xie, Huikang; He, Xian; Zhang, Yuan; Zhang, Aihong; Li, Huiping (Frontiers in Pharmacology, 2022)
It is generally accepted that the pathophysiology of idiopathic pulmonary fibrosis (IPF) can be attributed to impaired lung interstitium and alveoli, while airway involvement has rarely been reported. In the present study, we aimed to investigate the actual occurrence of IPF comorbid small airway dysfunction (SAD) and its impact on survival. Data from inpatients diagnosed with IPF at Shanghai Pulmonary Hospital (Shanghai, China) from 2011 to 2021 were retrospectively collected and analyzed. Lung function parameters were used to assess SAD. A total of 243 IPF patients were included in this retrospective study, and 84 cases (84/243, 34.57%) were diagnosed with SAD. The lung histopathology showed that all 48 cases undergoing lung transplantation presented various degrees of airway lesions, of which 18 patients (18/48, 37.5%) diagnosed with SAD before lung transplantation had a higher proportion of airway distortion and obliteration. The possible risk factors associated with IPF comorbid SAD were smoking, male, younger age, and high CT fibrosis and emphysema scores. By univariate Fine-Grey regression, the hazard ratio (HR) of IPF comorbid SAD was 1.725 (95% CI 1.071, 2.777, p < 0.05). After adjusting the CTPF model and GAP model, the value of HR was 1.714 (95% CI 1.043, 2.816, p < 0.05) and 1.731 (95% CI 1.074, 2.788, p < 0.05), respectively. These findings suggested that IPF comorbid SAD was an independent risk factor for the mortality of IPF patients.